ANALISIS KERUSAKAN MOTOR LISTRIK DENGAN METODE AGILE BERBASIS WEB PADA PT. CAHAYA HIDUP INDONESIA - Hermawan Setiawan; Ivan Fadila; Nova Indriani; Roeslan Djutalov (Journal of Research and Publication Innovation, 2025)
PT. Cahaya Hidup Indonesia is a private company specializing in the production of bicycle spare parts and supporting components. Currently, the quality check (QC) process in the company is still carried out manually using paper-based methods. This approach requires significant time and a high level of precision, increasing the risk of human error. Based on these challenges, a solution is needed in the form of an internal website application to enhance efficiency, accuracy, and reliability in the QC process. The application is designed using the System Development Life Cycle (SDLC) methodology with an Agile model. The system development employs a structured programming and analysis approach to facilitate the process. The technologies used include HTML, CSS, and JavaScript for the user interface development, and PHP along with MySQL for database management. The system is capable of recording and storing QC results data and generating statistical reports indicating whether the inspection outcomes are categorized as Not Good or OK. System testing is conducted using the Black Box Testing method to ensure all system functions operate as intended, and User Acceptance Testing (UAT) to gather user feedback regarding the system's usability and practicality. This application is expected to streamline the QC process, making it faster, more accurate, and more efficient while minimizing the risk of human error. Furthermore, the system aims to help the company improve productivity and the quality of services provided.